The risk of post-intensive care syndrome among patients hospitalised in the intensive care unit - Białek, Katarzyna (Medical Studies/Studia Medyczne, 2021)
The development of medicine and the improvement of techniques used for life support in intensive care units (ICUs) have significantly contributed to reducing the mortality of treated patients. On the other hand, many of them experience reduced quality of life and health problems after discharge from the unit. Individuals who have undergone a critical illness requiring intensive care have reported physical weakness, mental health problems, and a decrease in cognitive functions. It has been proposed that this form of reaction of patients treated in the ICU should be called post-intensive care syndrome (PICS). Understanding and early diagnosis of PICS may therefore be important for the medical personnel and for the patient and his/her family. This article describes the reactions and health consequences of patients treated in the ICU and how to prevent them.